Nitrate Metabolism Modulates Biosynthesis of Biofilm Components in Uropathogenic Escherichia coli and Acts as a Fitness Factor During Experimental Urinary Tract Infection - Martín-Rodríguez, Alberto J.; Rhen, Mikael; Melican, Keira; Richter-Dahlfors, Agneta (Frontiers in Microbiology, 2020)
To successfully colonize a variety of environments, bacteria can coordinate complex collective behaviors such as biofilm formation. To thrive in oxygen limited niches, bacteria’s versatile physiology enables the utilization of alternative electron acceptors. Nitrate, the second most favorable electron acceptor after oxygen, plays a prominent role in the physiology of uropathogenic Escherichia coli (UPEC) and is abundantly found in urine. Here we analyzed the role of extracellular nitrate in the pathogenesis of the UPEC strain CFT073 with an initial focus on biofilm formation. Colony morphotyping in combination with extensive mutational, transcriptional, and protein expression analyses of CFT073 wild-type and mutants deficient in one or several nitrate reductases revealed an association between nitrate reduction and the biosynthesis of biofilm extracellular matrix components. We identified a role for the nitrate response regulator NarL in modulating expression of the biofilm master regulator CsgD. To analyze the role of nitrate reduction during infection in vivo, we tested wild-type CFT073 and a nitrate reductase null mutant in an ascending urinary tract infection (UTI) model. Individually, each strain colonized extensively, suggesting that nitrate reduction is expendable during UTI. However, during competitive co-infection, the strain incapable of nitrate reduction was strongly outcompeted. This suggests that nitrate reduction can be considered a non-essential but advantageous fitness factor for UPEC pathogenesis. This implies that UPEC rapidly adapts their metabolic needs to the microenvironment of infected tissue. Collectively, this work demonstrates a unique association between nitrate respiration, biofilm formation, and UPEC pathogenicity, highlighting how the use of alternative electron acceptors enables bacterial pathogens to adapt to challenging infectious microenvironments.